Factor structure of time-sharing performance at different levels of practice - Jerneić, Željko (Array, 2007)
Previous attempts to identify a general time-sharing ability have been investigated at the low level of practice and have proven unsuccessful. Therefore, in the present study we examined whether the hypothetical time-sharing ability would emerge at a higher level of dual-task practice. To test this possibility, 111 participants performed various tracking and choice-reaction tasks during 10 consecutive days of practice both singly and concurrently. Under single-task conditions participants carried out seven simple tasks two times a day, while under dual-task conditions they carried out 14 different combinations of two simple tasks, three times each. This yielded 20 performance measures for each simple task and 30 performance measures for every dual-task combination. The data were analyzed with a series of factor analyses, separately for every level of practice: the low level (the first 3 days), intermediate level (the following 4 days), and high level one (during the last 3 days). The results showed that practice has no significant impact on the factor structure of single- and dual-task measures. Almost identical factor solutions have been obtained for all three levels of practice, and the general time-sharing factor representing hypothetical ability has not been identified at any level of practice. Instead, at all levels, three group time-sharing factors have been obtained. These findings support the idea of a multifactor model of time-sharing performance suggesting that performance on various multiple tasks would depend on several relatively independent time-sharing abilities.